Skeletal Muscle Mass Index Is Positively Associated With Bone Mineral Density in Hemodialysis Patients - Ito, Kiyonori; Ookawara, Susumu; Hibino, Yutaka; Imai, Sojiro; Fueki, Mariko; Bandai, Yusaku; Yasuda, Masatoshi; Kamimura, Tatsuya; Kakuda, Hideo; Kiryu, Satoshi; Wada, Noriko; Hamashima, Yuri; et al. (Frontiers in Medicine, 2020)
Background Patients with chronic kidney disease (CKD) are at risk for bone loss and sarcopenia because of associated mineral and bone disorders (MBD), malnutrition, and chronic inflammation. Both osteoporosis and sarcopenia are associated with a poor prognosis; however, few studies have evaluated the relationship between muscle mass and bone mineral density (BMD) in hemodialysis (HD) patients. The present study examined the association between skeletal muscle mass index (SMI) and BMD in the lumbar spine and femoral neck in HD patients. Methods Fifty HD patients (mean age, 69 ± 10 years; mean HD duration, 9.0 ± 8.8 years) in Minami-Uonuma City Hospital were evaluated. BMD was measured by dual-energy X-ray absorptiometry, and SMI was measured by bioelectrical impedance analysis (InBodyTM) after HD. The factors affecting lumbar spine and femoral neck BMD were investigated, and multivariate analysis was performed. Results In simple linear regression analysis, the factors that significantly affected the lumbar spine BMD were sex, presence of hypertension, presence of diabetes mellitus, body mass index, triglyceride level, grip strength, and SMI; the factors that significantly affected the femoral neck BMD were sex, HD duration, serum creatinine level, tartrate-resistant acid phosphatase 5b level, undercarboxylated osteocalcin (ucOC) level, N-terminal propeptide of type I procollagen level, grip strength, and SMI. In multivariate analysis, SMI (standardized coefficient: 0.578) was the only independent factor that affected the lumbar spine BMD; the independent factors that affected the femoral neck BMD were SMI (standardized coefficient: 0.468), ucOC (standardized coefficient: -0.366) and sex (standardized coefficient: 0.231). Conclusion SMI was independently associated with the BMD in the lumbar spine and femoral neck in HD patients. The preservation of skeletal muscle mass could be important to prevent BMD decrease in HD patients, in addition to the management of CKD-MBD.